An experimental study of frost formation on cryogenic surfaces under natural convection conditions. (June 2016) - Liu, Zhongliang; Dong, Yuwan; Li, Yanxia
Highlights: An experimental system of frost deposition on cryogenic-temperature surfaces was set up. Liquid air was first formed on cryogenic-temperature surface before frost crystals appeared. Frost crystal clusters deposited on liquid air droplets are not static, they keep moving. Under very low surface temperature, as surface temperature drops, the frost layer thickness decreases. Abstract: An experimental system of frost deposition on cryogenic-temperature surfaces under natural convection conditions was set up and a series of frost formation experiments were conducted under various conditions, focusing on the frosting phenomena on horizontally- and vertically-placed cryogenic-temperature surfaces under natural convection conditions especially the early stage frost formation phenomena. The influences of surface temperature, air temperature and air relative humidity were also carefully studied of frost formation on vertical cryogenic surfaces. A very peculiar and important phenomenon for frost formation on cryogenic-temperature surfaces observed is that liquid air droplets were first formed on cryogenic-temperature surface if surface temperature is lower than −165 °C before frost crystals appeared. The liquid droplets on horizontally-placed surfaces may exist for a quite long time and even form a continuous film, and have significant influences on frost deposition. It was found that frost crystal clusters deposited on liquid air droplets are not static, they moves both as and relatively to the droplets. The frost layer growth on the vertical surfaces of cryogenic-temperature is highly non-uniform and exists a downward growth period during which the frost layer grows mainly along the downward direction of the vertical surfaces. It was also found that under very low surface temperature and natural convection conditions, as the surface temperature drops, the frost layer thickness decreases. This is completely different to the phenomenon observed on ordinary low-temperature cold surfaces.